Enhancing COVID-19 (COVID-19/SARI/SVP) pandemic preparedness: Assessment of testing and treatment capacity of the health facilities in Can Tho City, Vietnam in 2023 - Tuan, Le Van; Ngan, Ho Thi Thien; Anh, Nguyen Thi Quynh; Chinh, Dang Van; Huy, Nguyen Quang; Truc, Huynh Minh; Chinh, Tran Truong; Nghia, Nguyen Nhan; Cuong, Hoang Quoc; Giang, Pham Phu Truong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Vietnam was amongst the top fifteen countries most affected by COVID-19 pandemic in 2021 and 2022. Within Vietnam, Can Tho City witnessed a high case fatality rate at about 12.5 per 1,000 cases, which was higher than that of the nation's average death rate of 3.7 per 1,000 cases. This study aims at evaluating the COVID-19 tests and assessing the capacities of healthcare facilities (HFs) to prepare plans and robust health systems in strengthening pandemic response. We conducted a survey in September 2023 across 53 out of total 130 HFs in Can Tho City, including both private and public hospitals at central, provincial and district level. There were nine different aspects in each HF that worth evaluating whether: namely bed capacity, human resources, hospital capacity for receiving new patients, current treatment approaches for mild/moderate/severe/critical ill patients, medication management capacities, medical supplies and equipment, laboratory testing capacities, infection prevention and control, and communicable disease reporting. Results revealed that regarding the overall capacity, under normal condition, only 1.9% of healthcare facilities (HFs) met the standards for strong capacity, 52.8% with satisfactory capacity and the remaining 30.2% showed unsatisfactory capacity management. Conversely, during the COVID-19 pandemic, no HF reached our expectations for hospital capacity, whereas 52.8% had satisfactory capacity and 32.1% had unsatisfactory capacity. Furthermore, the insufficiency of appropriate medications can be seen in 72% of HFs, 45% HFs had limited testing capabilities, 42% HFs need to optimize hospital bed capacity and 43% struggled to cope with severe cases. Regular assessment plays a vital role in improving the overall pandemic preparedness, especially during the waves of COVID-19 infection, the appearance of new coronavirus variants and increasing virulence of the virus. The coordination at the national level to implement such assessments will bolster future pandemic preparedness and response.